Development of pedagogical competences for future primary school teachers through distance learning - Otynshina, Galiya; Dusembinova, Raifa; Odintsova, Svetlana; Aidarbekova, Kulzhan; Shaushekova, Bayan (Jurnal Cakrawala Pendidikan, 2024)
This work aims to identify effective means of distance learning methods for developing pedagogical competence among student-teachers. To achieve this goal, the study applies various methods and approaches, including dialectical and functional methods, alongside analysis and synthesis, pedagogical observation, comparison, and classification. The research employed these methodologies to analyze existing literature and explore best practices in distance learning for teacher training. The research yielded significant theoretical and practical contributions. The theoretical foundation strengthens the understanding of how distance learning can foster pedagogical competence. The practical value lies in its potential application as both instructional and methodological material for training future teachers. It can also serve as a tool for practicing educators to improve their skills by familiarizing them with effective distance learning tools and strategies. Future research should explore the evolution of distance learning methods in teacher training, identify potential shortcomings of distance learning approaches, and propose effective solutions to overcome these limitations.